Professional Active Server Pages 2.0 - Fedorov, Alex. (Birmingham, [England] : Wrox Press, 1998)
Active Server Pages is part of Microsoft's server-based technology. It enhances HTML pages for a Web or corporate intranet.
Includes index.
'Active Server Pages ... has improved in version 2.0 ...'--[p. 1].
Keywords: Active server pages; Web sites -- Design; Intranets (Computer networks) -- Case studies; Web servers -- Computer programs